Histopathological features of salivary gland tumors: A single-center experience - Senel, Fatma; Karaman, Hatice (Annals of Medical Research, 2021)
Aim: This study’s goal was to retrospectively evaluate cases who were diagnosed with primary salivary gland tumors in our center, to examine the histopathological features of these tumors, and to reveal difficulties in the differential diagnosis. Material and Methods: Sixty-four patients who applied to our center with complaints of pain and swelling in the salivary gland region between January 2016 and February 2020 and who were diagnosed with salivary gland tumor in our pathology clinic were analyzed retrospectively. The age and sex of the patients, the salivary gland where the tumor was located, and the histopathological examination results were recorded. Results: The age range of the patients was 13-89 years, and 57.8% and 42.2% of 64 patients in total were female and male, respectively. While 86% of the patients had tumors located in the parotid gland, 14% of them had tumors located in the submandibular gland. According to the histopathological examination results, 89% and 11% of the patients had benign and malignant tumors, respectively. While the most common tumor among benign tumors was a pleomorphic adenoma at a rate of 57.8%, the most common tumor among malignant tumors was a mucoepidermoid carcinoma at a rate of 4.7%. Conclusion: In the present study, salivary gland tumors were more common in females. The majority of salivary gland tumors were located in the parotid gland, and the majority of them were benign. The majority of tumors located in the submandibular gland were malignant.
Keywords: Histopathology; salivary gland; tumor